Rheumatic Fever (RF) and Rheumatic Heart Disease (RHD) Prevention and COntrol Program in Nepal. - Regmi, Prakash Raj; Upadhyaya, AB (Nepalese Heart Journal, 2017)
Ministry of Health and population, Government of Nepal announced the launch of National program for prevention and control of RF/RHD in Nepal in Ashad 2063 BS. Implementation of this program started on 15 Ashad 2064 with technical and organization support from Nepal Heart Foundation. Budget allocated for this Program in fiscal year 2063/064 was Nrs. 30 Lakhs, in 2064/065 Nrs. 40 Lakhs and in 2065/66 Nrs 10 Lakhs. This is the first program in Nepal launched by the government for prevention & control of heart disease. Nepal Heart foundation is the main authorizedvorganization for implementation of this program.